PENGARUH KEPEMIMPINAN DAN PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR CAMAT SUNGAI MANDAU KABUPATEN SIAK - Ningsih, Dewita Suryati; Pramadewi, Arwinence; ', Syahril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was carried out on sub-district office employees Sungai Mandau in the village of Muara Kelantan jl. H. Abdurrahman. This study aims to determine how the Effect of Leadership and supervision either simultaneously or partially to discipline employees working at the district office Sungai Mandau Siak. The population in this study were employees of the district office Sungai Mandau Siak district, amounting to 32 people. While the overall sample of the population in this study, the method of analysis used is descriptive quantitative method by using SPSS version 18. From the results of testing that has been done, simultaneous regression test (F test) showed that the leadership and supervision of simultaneous positive and significant effect on labor discipline. The results of the partial regression test (t test) showed that the variables Leadership and Supervision in partial positive and significant impact on employee discipline variable.Keywords: Leadership, supervision and discipline of work